2014
DOI: 10.1021/la501416u
|View full text |Cite
|
Sign up to set email alerts
|

Transition from Stripe-like Patterns to a Particulate Film Using Driven Evaporating Menisci

Abstract: Better control of colloidal assembly by convective deposition is particularly helpful in particle templating. However, knowledge of the different factors that can alter colloidal patterning mechanisms is still insufficient. Deposit morphology is strongly ruled by contact line dynamics, but the wettability properties of the substrate can alter it drastically. In this work, we experimentally examined the roles of substrate contact angle hysteresis and receding contact angle using driven evaporating menisci simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…As the solution is sheared over the wafer, the solution contact line (air/liquid/solid interface) is pinned on the solvent‐wetting regions, while less/no pinning occurs on the solvent‐dewetting regions. Previous literature has shown that contact line pinning is important for forming well‐packed particles . When the contact line is pinned, the evaporation rate is accelerated at the contact line, which causes edgeward convective flow and transport of both solvent and SWCNTs towards the contact line .…”
mentioning
confidence: 99%
“…As the solution is sheared over the wafer, the solution contact line (air/liquid/solid interface) is pinned on the solvent‐wetting regions, while less/no pinning occurs on the solvent‐dewetting regions. Previous literature has shown that contact line pinning is important for forming well‐packed particles . When the contact line is pinned, the evaporation rate is accelerated at the contact line, which causes edgeward convective flow and transport of both solvent and SWCNTs towards the contact line .…”
mentioning
confidence: 99%
“…17,18 To overcome this effect, several techniques have been proposed by manipulating capillary flows, changing the particle shape and modifying the surface wettability of the substrate. 11,[19][20][21][22][23][24][25] However, the ability to dynamically control the distribution of the suspended particles during evaporation of droplets has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, evaporative self-assembly is a promising method in which the nanoparticles can be assembled into a variety of patterns by manipulating parameters such as the evaporation rate, Marangoni effects, etc. For instance, on a planar surface, the self-assembly of micrometer size band structures have been observed in the literature. Such patterns are believed to originate from the pinning of the contact line of a droplet during the evaporation process, which causes the accumulation of the particles near the contact line in a so-called coffee ring effect. , As the suspension evaporates, the contact line depins before it is pinned again at the next position, and in this sequential way, stripes or multiple irregular rings are formed …”
Section: Introductionmentioning
confidence: 99%